Algebra 2 Common Core

Published by Prentice Hall
ISBN 10: 0133186024
ISBN 13: 978-0-13318-602-4

Chapter 6 - Radical Functions and Rational Exponents - 6-2 Multiplying and Dividing Radical Expressions - Practice and Problem-Solving Exercises: 33

Answer

$-2x^2y\sqrt[3]{30x}$

Work Step by Step

RECALL: $\sqrt[3]{a} \cdot \sqrt[3]{b} = \sqrt[3]{a\cdot b}.$ Use the rule above to have $-2\sqrt[3]{(2x^2y^2)(15x^5y)} \\=-2\sqrt[3]{30x^7y^3} \\=-2\sqrt[3]{x^6y^3(30x)} \\=-2\sqrt[3]{(x^2y)^3(30x)} \\=-2(x^2y)\sqrt[3]{30x} \\=-2x^2y\sqrt[3]{30x}.$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.